Corruption in Education Systems: A Review of Practices, Causes, Effects and Recommendations - Sergio Cárdenas Denham (Universidad Autónoma de Baja California, 2012)
Achieving higher levels of transparency and accountability in education systems is essential for attaining an adequate distribution of educational opportunities. Studies of corruption in education systems are important since they can contribute to increasing public awareness of the harmful effects of corruption and promote political support for the implementation of anti-corruption initiatives in education. This paper describes a typology of corrupt practices and develops a classification for the findings reported in the literature on corruption in education, such as causes, consequences and recommendations, as well as a classification of the methodologies applied to the study of corrupt practices. Finally, it describes the possible implications of these findings for policymakers.